Preserving nanoscale features in polymers during laser induced graphene formation using sequential infiltration synthesis - David S. Bergsman (Nature Portfolio, 2020)
High temperatures induced during lasing can deform the substrate polymer used for fabrication of electrically conductive membranes. Here, the authors show that sequential infiltration synthesis of alumina stabilizes polyethersulfone (PES) membranes against deformation above the polymers’ glass transition temperature.